Application of diffusion tensor imaging (DTI) and MR-tractography in the evaluation of peripheral nerve tumours: state of the art and review of the literature - Bruno, Federico; Arrigoni, Francesco; Mariani, Silvia; Patriarca, Lucia; Palumbo, Pierpaolo; Natella, Raffaele; Ma, Liheng; Guglielmi, Giuseppe; Galzio, Renato J; Splendiani, Alessandra; Di Cesare, Ernesto; Masciocchi, Carlo; et al. (Acta Biomedica Atenei Parmensis, 2019)
Peripheral nerves can be affected by a variety of benign and malignant tumour and tumour-like lesions. Besides clinical evaluation and electrophysiologic studies, MRI is the imaging modality of choice for the assessment of these soft tissue tumours. Conventional MR sequences, however, can fail to assess the histologic features of the lesions. Moreover, the precise topographical relationship between the peripheral nerve and the tumor must be delineated preoperatively for complete tumour resection minimizing nerve damage. Using Diffusion tensor imaging (DTI) and tractography, it is possible to obtain functional information on tumour and nerve structures, allowing the assess anatomy, function and biological features. In this article, we review the technical aspects and clinical application of DTI for the evaluation of peripheral nerve tumours.